Hubungan Kebiasaan Bermain Game Online dan Motivasi Belajar dengan Hasil Belajar Tematik Peserta Didik Kelas V SD Negeri se-Gugus Diponegoro Kecamatan Metro Selatan - Muhisom; Hariyanto; Astuti, Nelly; Darsono (Pedagogi: Jurnal Pendidikan Dasar, 2023)
The problem in this study is the habit of playing online games and learning motivation as well as their relationship with thematic learning outcomes of students in class V SD Negeri as Diponegoro Cluster, Metro Selatan District, Metro City. This study aims to determine a significant relationship between the habit of playing online games and learning motivation with thematic learning outcomes. The type of research is ex-postfacto correlation. The population amounted to 59 students and all populations were used as research samples. The data collection instrument is a questionnaire with a Likert scale, which was previously tested for validity and reliability. Data analysis using product moment correlation. Based on the analysis conducted, the research results can be concluded that there is a positive and significant relationship between the habit of playing online games with the thematic learning outcomes of students, indicated by the correlation coefficient being at the "Strong" level, there is a positive and significant relationship between learning motivation with the students' thematic learning outcomes indicated by the correlation coefficient being at the "strong" level, there is a positive and significant relationship between the habit of playing online games with learning motivation with the correlation coefficient being at the "strong enough" level, there is a positive and significant relationship between habits playing online games and learning motivation with thematic learning outcomes of students shown by the correlation coefficient is at the level of "Strong".